Morphine signaling in Bos taurus and Equus caballus - Mantione, Kirk J. (Archives of Medical Science, 2009)
The presence of morphine and the mu opioid receptor has been demonstrated in cells from the nervous, endocrine, immune, vascular, reproductive, respiratory, and digestive systems of mammals. The understanding of morphinergic signaling in domestic animals is vital for properly managing this commercially valuable resource. This review discusses the known functions of mu opioid receptors in Bos taurus and Equus caballus. Morphine has been shown to regulate the release of hormones and neurotransmitters in these animals in diverse tissues. The mu opioid receptor is also present on equine gametes and controls key functions of these reproductive cells. Evidence for the presence of the mu opioid receptors in bovine blood, heart, spleen and bone marrow is discussed. Given the widespread occurrence of mu opiate processes it is surmised that it transcend functions only focused on pain.